Health benefits and control costs of tightening particulate matter emissions standards for coal power plants - The case of Northeast Brazil. (March 2019) - Howard, Daniel B.; Thé, Jesse; Soria, Rafael; Fann, Neal; Schaeffer, Roberto; Saphores, Jean-Daniel M.
Abstract: Exposure to ambient particulate matter (PM) caused an estimated 4.2 million deaths worldwide in 2015. However, PM emission standards for power plants vary widely. To explore if the current levels of these standards are sufficiently stringent in a simple cost-benefit framework, we compared the health benefits (avoided monetized health costs) with the control costs of tightening PM emission standards for coal-fired power plants in Northeast (NE) Brazil, where ambient PM concentrations are below World Health Organization (WHO) guidelines. We considered three Brazilian PM10 (PM x refers to PM with a diameter under x micrometers) emission standards and a stricter U.S. EPA standard for recent power plants. Our integrated methodology simulates hourly electricity grid dispatch from utility-scale power plants, disperses the resulting PM2.5, and estimates selected human health impacts from PM2.5 exposure using the latest integrated exposure-response model. Since the emissions inventories required to model secondary PM are not available in our study area, we modeled only primary PM so our benefit estimates are conservative. We found that tightening existing PM10 emission standards yields health benefits that are over 60 times greater than emissions control costs in all the scenarios we considered. The monetary value of avoided hospital admissions alone is at least four times as large as the corresponding control costs. These results provide strong arguments for considering tightening PM emission standards for coal-fired power plants worldwide, including in regions that meet WHO guidelines and in developing countries. Graphical abstract: Health benefits and control costs of tightening PM10 standards for coal power plants in NE Brazil.Unlabelled Image Highlights: We compare health benefits and control costs of tightening PM10 emissions standards. We model electricity generation in NE Brazil and focus on coal power plants. In our study area, PM concentrations are below WHO guidelines. We combine an hourly dispatch model with dispersion and health assessment models. Benefits of tighter PM10 emission standards exceed control costs by a factor > 60.